Testing the triple-match principle among Dutch elite athletes: A day-level study on sport demands, detachment and recovery. (November 2017) - Balk, Yannick A.; de Jonge, Jan; Oerlemans, Wido G.M.; Geurts, Sabine A.E.
Abstract: Objectives: Detachment, getting a physical, cognitive, and emotional break from the effortful demands of training and competition, is a recovery experience that can buffer the adverse effects of high sport demands on health and well-being. The matching hypothesis states that recovery strategies are most effective when they match particular sport demands. The main aim of this study was to investigate the matching hypothesis with respect to the relation between daily sport demands, detachment, and recovery state among elite athletes. Design: A one-week online daily diary study was conducted. Multilevel regression analyses tested within-subject associations between daily sport demands, detachment, and recovery state at bedtime, while controlling for recovery state in the morning. Method: Sixty-eight elite athletes completed a daily diary survey after waking up (T1) and at bedtime (T2) across eight consecutive days. Results: Results showed that daily physical detachment was positively related to daily physical recovery, whereas daily emotional detachment was positively related to daily cognitive recovery and emotional recovery. Moderating effects of daily detachment on the relation between daily sport demands and daily recovery state occurred more often when there was a match between specific types of sport demands, detachment, and recovery state rather than when there was less match or no match. Conclusions: Findings indicate that physical and emotional detachment are effective recovery strategies for elite athletes. Moreover, it is important that detachment matches the type of effort that has been spent to find the strongest stress-buffering effects. Highlights: Daily physical detachment was positively related to daily physical recovery, whereas daily emotional detachment was positively related to daily cognitive recovery and to daily emotional recovery. Athletes who have been confronted with high emotional sport demands benefit from ways to let go of negative sport-related emotions. The results support the idea that detachment is most effective when it matches the main source of sport demands. This study underscores the usefulness of models stemming from organizational psychology for the elite sport domain.